2012
DOI: 10.1055/s-0040-1703561
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Effect of Ambulation and Birthing Ball on Maternal and Newborn Outcome Among Primigravida Mothers in Selected Hospitals in Mangalore

Abstract: The study was conducted to assess the effect of ambulation and birthing ball on the maternal and newborn outcome from 01.08.2011 to 31.10.2011. This randomized control study was conducted on 60 primigravida mothers. Purposive sampling technique was used for the selection of samples followed by random allocation of 20 samples each to the three groups namely, ambulation, birthing ball and control group respectively using lottery method. Ambulation and birthing ball therapy were given to the respective samples be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 1 publication
4
31
1
6
Order By: Relevance
“…Also these findings supported by Hodnett et al [10] who found that women who encouraged to assuming upright position were satisfied and more comfortable. On the other hand this findings disagree with Mathew et al [27] who found that women who were choosing side lying or lying on back in first stage of labor were more satisfied.…”
Section: Discussioncontrasting
confidence: 83%
“…Also these findings supported by Hodnett et al [10] who found that women who encouraged to assuming upright position were satisfied and more comfortable. On the other hand this findings disagree with Mathew et al [27] who found that women who were choosing side lying or lying on back in first stage of labor were more satisfied.…”
Section: Discussioncontrasting
confidence: 83%
“…In partial agreement with our findings study by Mathew, 2012 [33] who stated that there is significant improvement in maternal outcome after the use of birthing ball therapy while 95% of birthing ball group underwent normal vaginal delivery. As well, the same outcomes indicated that, there is significant difference in second stage duration whereas no significant difference in first stage duration and cervical dilatation rate.…”
Section: Discussionsupporting
confidence: 93%
“…Eventually our findings pointed to approximately 70% of the women who adopted birth ball during first stage were satisfied regarding the care received in first stage of labor, compared to 25% of women in control group exhibit high satisfaction. In concordance with these results Mathew , 2012 [33] study concluded that 95% of mothers from ambulation group and 95% mothers from birthing ball group, were comfortable and satisfied and would like to recommend birthing ball use to others .…”
Section: Discussionmentioning
confidence: 62%
“…The review showed that using a flexible sacrum position can reduce the duration of the second stage of labor by 21.12. The reduction was contributed mainly by a large reduction in the three studies of the birthing ball, flexible sacrum and squatting positions reduce 25.9, 29.7 and 34.38 minutes respectively (22,27,28). The reduction in duration is in line with other review and meta-analysis conducted both in UK in different times (29,30), in contrast other meta-analysis done in Australia and UK, didn't show any reduction in duration of second stage (14,31).…”
Section: Discussionsupporting
confidence: 78%